Comparison Study between Clinical and Environmental Isolates of Pseudomonas aeruginosa in terms of Pro-inflammatory Cytokines Production in Mice Lungs (World Journal of Experimental Biosciences, 2023)
Pseudomonas aeruginosa is one of the most widespread bacteria. It causes infectious diseases and at the same time is found in soil and water. It stimulates the pro-inflammatory immune response. The study aims to compare the role of P. aeruginosa isolated from infected burned wounds and that isolated from fresh water in terms of stimulating the pro-inflammatory response of the respiratory tract. In the current study, P. aeruginosa isolates were isolated from infected burned wound swabs (PAC) and from freshwater (PAE). Laboratory mice were stimulated by giving them intranasal (i.n.) standard inoculum of pathogenic and environmental isolates of P. aeruginosa (PAC and PAE respectively). The levels of interleukin (IL-) 1 and tumor necrosis factor (TNF)-alpha (α) were measured in the homogenized mice lungs. The study demonstrated that both isolates (PAC and PAE) stimulated the respiratory system to secrete pro-inflammatory cytokines (IL-1β and TNF-α). Both isolates significantly (P<0.05) increased the level of IL-1β and TNF-α at the first-hour post-administration, and the highest level was observed at the fourth hour after administration with PAC and PAE. After that, the level of cytokines decreased dramatically over time. At 48 hours after administration, it was found that a significant increase of IL-1β and TNF-α was seen only in the lungs of the mice that were given the pathogenic isolates. It can be concluded that both isolates of P. aeruginosa (PAC and PAE) stimulate respiratory system cells to produce pro-inflammatory cytokines, but PAC stimulates mice lungs to produce IL-1β and TNF-α in a higher level and for a longer period as compared with stimulation of mice lungs with PAE.